FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGEMUDI TERHADAP PENERAPAN SMITH SYSTEM DI PT. SUCOFINDO CABANG PEKANBARU - Ari Omar Mochtar; Siswi Jayanti; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Smith system is a driving system that allows the drivers to to avoid accidents in driving. Based on investigation result of 7 accident cases that occurred in PT. Sucofindo Pekanbaru Branch in the last 3 years were due to drivers non-compliance in practising Smith system. The purpose of this study is to analyze factors related to drivers compliance towards the application of Smith system in PT. Sucofindo Pekanbaru Branch. The design of this study is quantitative with cross sectional approach. The study population is 32 drivers and inspectors. Sampling method used is Total Sampling. Data collecting conducted by inquiries filled by the subjects. The data analysis using univariate and bivariate analysis using chi square test. The result of statistical test showed that the relating variables were Attitude (p=0,011), Training (p=0,026), Knowledge (p=0,028), while the unrelating variables were Road Condition (p=0,152), Social Support (p=0,217), and Age (p=0, 681). The management are recommended to review the performance of training programs held, and implement Stop Work Authority (SWA) program as a form of performance supervision of drivers PT. Sucofindo Pekanbaru’s operational car.